The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jmhi.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR absorbing quantum dots might be usable for growth factor-based differentiation of stem cells

Abstract: For stem cell therapy of degenerative diseases, it is necessary to differentiate stem cells into the specific lineage. There are several growth factors which have been used for differentiation of stem cells. Some growth factors can dose-dependently induce differentiation of stem cells so that the increase of growth factor concentration results in production of the higher level of differentiated cells. However, due to the toxicity of some differentiation factors (e.g. retinoic acid), the lower dose of growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Like specific substrates and scaffolds, growth factors possess a significant role in stem cell differentiation. 11 It has been shown that the combination of both scaffold and growth factors can facilitate the orientation of stem cells toward target lineages. Particular physicochemical properties of ECM dictate specific cell responses by engaging relevant signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Like specific substrates and scaffolds, growth factors possess a significant role in stem cell differentiation. 11 It has been shown that the combination of both scaffold and growth factors can facilitate the orientation of stem cells toward target lineages. Particular physicochemical properties of ECM dictate specific cell responses by engaging relevant signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…But, Brownian motion of growth factors in the medium leads only a small amount of them to reach biological signal pathway cell receptors. Hence, even if a large amount of growth factors is added to culture medium, only a small portion is involved in the differentiation of stem cells (9). Moreover, stem cells can be stimulated by chemical or topographical cues (10).…”
Section: Introductionmentioning
confidence: 99%